Evaluation of the Efficacy of Miira-Cell, a Novel Nutraceutical, in Reducing High-Fat Diet-Induced Hypercholesterolemia in Wistar Rats - Chioma Cordelia Ugwu; Stanley Obinna Ezeadichie; Okey John Nnamani; Osah Martins Onwuka; Chioma Marylyn Adilieje (Biology, Medicine, & Natural Product Chemistry, 2026)
Hypercholesterolemia is a major risk factor for cardiovascular diseases, often exacerbated by high-fat diets. Miira-Cell, a novel nutraceutical, has been developed to address this issue. This study evaluates the efficacy of Miira-Cell in mitigating hypercholesterolemia induced by high-fat diet in Wistar rats. Acute toxicity testing showed that Miira-Cell was safe, with an LD50 greater than 5000 mg/kg. Thirty Wistar rats were divided into six groups: normal control, high-fat diet control, and three groups receiving high-fat diets supplemented with low, medium, and high doses of Miira-Cell, respectively. A sixth group received Rosuvastatin as a positive control. After a 14-day treatment period following a 21-day high-fat diet, lipid profiles, liver biomarkers, oxidative stress markers, and cardiac tissue histopathology were assessed. The results showed that Miira-Cell significantly reduced triglycerides, VLDL, and total cholesterol in a dose-dependent manner, similar to Rosuvastatin. Both Miira-Cell and Rosuvastatin also lowered LDL levels. However, all treatment groups showed decreased HDL levels, which may indicate potential effects on HDL metabolism. Miira-Cell demonstrated hepatoprotective properties by reducing liver enzyme levels and oxidative stress. Histopathological analysis revealed tissue damage in the negative control group, while tissue integrity was preserved in Miira-Cell and Rosuvastatin-treated groups. In conclusion, Miira-Cell shows potential as a therapeutic agent for hypercholesterolemia and associated liver diseases, although further research is necessary to elucidate its mechanisms and clinical applicability.